REALISASI BENTUK TINDAK TUTUR DIREKTIF DALAM PERISTIWA RAPAT DINAS DI LINGKUNGAN PEMERINTAHAN KOTA BERBUDAYA JAWA - Harun Joko Prayitno; Malikatul Laila; . Sumarlam (Universitas Muhammadiyah Surakarta, 2007)
The study is about the use of directive speech act or Tindak Tutur Direktif (TTD) in the official meeting events held in the vicinage of Javanese culture civic government by using a gender approach. The data were collected by using the basic techniques of recording and was continued to open listening for participant-interview. The collected data were analyzed by using the techniques of intra-lingual and extra-lingual comparison together with the analysis method of means-end. The result shows that, first, the forms of TTD can be classified into 9 categories: (1) to request, (2) to advise, (3) to lead, (4) to support, (5) to interfere, (6) tooffer, (7) to offend, (8) to hinder, and (9) to counter. Second, based on the technique of speaking, female speakers or penutur Pejabat Perempuan (nPP) use the technique of literal speaking (37,65%) and the non-literal one (62,35%). Based on the technique of sending meaning, male speakers or penutur Pejabat Lelaki (nPL) use the technique of literal speaking (39,68%) and the non-literal one (60,32%). Both nPP and nPL use non-literal techniques more than literal ones. Third, based on the speaking strategy, nPP chooses direct strategy (38,82%) and indirect one (61,18%). Meanwile, the speaking strategy chosen by nPL, is (40,48%) for direct strategy and (58,73%) for indirect one. Therefore, the officialsprefer using indirect strategies in speaking. Finally, factors influencing the forms of the officials’s TTD are: (1) who the second persons are, (2) what the social relation is between nPP/nPL and the meeting audience, (3) what the social-societal status of nPP/ nPL is; and (4) the topic being discussed.